Homocysteine, migration and early vascular impairment in people of African descent. Issue 9 (10th December 2007) - Kalra, L; Iveson, E; Rambaran, C; Sherwood, R; Chowienczyk, P; Ritter, J; Shah, A; Forrester, T
Abstract : Objectives: A gradient of increased vascular risk with migration exists across the African diaspora. We investigated the hypothesis that differences in homocysteine/folic acid status contribute to this increased risk. Design: Community cohort study of 73 Afro-Caribbeans in the United Kingdom and 151 matched Afro-Caribbeans in Jamaica with no conventional vascular risk factors. Methods: Subjects were compared for baseline characteristics, vascular risk profile, homocysteine (tHcy), folate and B12 concentrations. Endothelium-dependent vasodilatation was assessed by measuring the absolute change from baseline in the reflection index (RI) of the digital volume pulse during intravenous infusion of albuterol (5 μg/min, ΔRIALB ) and glyceryltrinitrate (GTN) (5 μg/min, ΔRIGTN ). Carotid intima media thickness (CIMT) was measured ultrasonographically in the distal 1 cm of the common carotid artery. Results: UK Afro-Caribbeans had higher tHcy (mean difference 2.3 (95% confidence interval 1.3 to 3.4) μmol/l) and lower folate (mean difference 3.2 (95% CI 1.8 to 4.7) μg/l) levels. ΔRIALB was 5.1 (95% CI 2.5 to 7.6) percentage points lower and CIMT 0.124 (95% CI 0.075 to 0.173) mm greater in UK Afro-Caribbeans. Higher tHcy and lower folate concentrations correlated with impaired ΔRIALB and increased CIMT. A 1 μg/l increase in folate concentration was associated with 0.3 (95% CI 0.1 to 0.5) percentage point increase in ΔRIALB and 0.002 (95% CI 0.001 to 0.006) mm decrease in CIMT, independent of blood pressure, smoking and vascular risk profile. Conclusions: Lower folate concentrations in UK compared with West Indian African-Caribbeans may contribute to the higher stroke risk seen in UK African-Caribbean people.